PENGARUH CUSTMOR REVIEW, CUSTOMER RATING DAN PROMOSI GRATIS ONGKOS KIRIM TERHADAP KEPUTUSAN PEMBELIAN - siregar, gusnaini; Husda, Nur Elfi (SCIENTIA JOURNAL, 2023)
This research was conducted to see the influence exerted on consumer purchasing decisions through online customer reviews, online customer ratings, and free shipping promotions. This study used a qualitative approach which is a data processing using the SPSS 22 application. The population in this study were shoppee users in Buliang Village, Batu Aji District, Batam City by taking Unknown Populations as a sample so that 96 respondents were rounded up and 100 people were rounded up. Data collection techniques in this study used multiple linear regression data techniques. The results of this study indicate that online customer reviews have a positive and significant effect on purchasing decisions. Online customer ratings have a positive and significant effect on purchasing decisions. Free shipping promotions have a positive and significant effect on purchasing decisions.